Development and evaluation of rapid and simple detection of Klebsiella pneumoniae using closed dumbbell-mediated isothermal amplification diagnostic assay - Zhang, Yanli; Chen, Xuhan; Ouyang, Guifang; Wang, Jiaping; Sun, Yongcheng; Lai, Yanli; Zhang, Ping; Guo, Fei; Yang, Shujun; Mao, Rui (Frontiers in Microbiology, 2024)
Klebsiella Pneumoniae (K. pneumoniae) is the most common pathogen causing hospital respiratory tract infection and epidemic. Gold standard procedures of microscopic examination and biochemical identification are widely used in clinical diagnosis with disadvantages of low sensitivity, time-consuming and sophisticated equipment requiring. An efficient, nucleic acid amplification-based sensitive and specific on-site identification of K. pneumoniae in clinical is necessary to facilitate clinical medication and disease control. We developed a closed dumbbell mediated isothermal amplification (CDA) assay for the rapid and sensitive detection of conserved rcsA gene of K. pneumoniae by real-time fluorescence monitoring and end-point colorimetric judgement. We designed and selected a pair of inner primers of CDA to detect K. pneumoniae. Then outer and loop primers were designed and verified to accelerate CDA reaction to achieve more efficient detection of K. pneumoniae. The results showed the detection limit of CDA assay was 1.2×10-5 ng/μL (approximately 1 copy of the target gene) within 60 min, which was 100-fold more sensitive than real-time quantitative PCR (qPCR). Several pathogen genomic DNAs (Staphylococcus aureus, Shigella sonnei, Vibrio parahaemolyticus, Escherichia coli, Candida glabrata, Candida tropicalis, Candida parapsilosis, Candida albicans, Streptococcus agalactiae, Rickettsia, Listeria monocytogenes, Pseudomonas aeruginosa, Klebsiella oxytoca, and Klebsiella aerogenes) were used to evaluate the sensitivity and specificity of the established K. pneumoniae CDA assay. Total 224 batches of samples from other strains tested were negative and 296 batches of extracted K. pneumoniae DNA samples were positive by the developed CDA amplification approach, revealing high specificity and specificity of the diagnostic assay. In addition, the results of real-time fluorescence amplification of the K. pneumoniae CDA were in consistent with those of end-point colorimetric results. In conclusion, the established real-time fluorescence and visual CDA assays of K. pneumoniae with merits of rapid, sensitive and specificity could be helpful for on-site diagnosis and clinical screening in rural areas.